Analisis Gambar Ekspresi Diri Siswa Kelas III Di SD 2 Jepang Pakis - Wijayanto, Wasis; Maghfiroh, Anif; Rizky, Reina; Pramudita, Diah Ayu; Laila, Naimatul (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2025)
This study aims to analyze the drawings of grade III students of SD 2 Jepang Pakis in expressing themselves through works of art. This study is motivated by students' works of art in the form of self-expression drawings in drawing activities in art and culture learning. The research method used is qualitative through a case study approach with grade III students as research subjects. Data were analyzed through direct observation and in-depth interviews with class teachers. The results of the study showed an interesting phenomenon, namely the uniformity of the drawing themes that were quite striking even though students were given the freedom to express themselves individually. Some students were able to produce works that expressed themselves and reflected their individuality, but the majority of works tended to be homogeneous, and this event is worthy of further study. The conclusion of this study confirms that students' works of art indicate certain factors that may influence students' choice of drawings, such as the influence of the surrounding environment, the way teachers introduce art, or even the influence of peers.